Clinical self-efficacy and illness beliefs in ambiguous chronic pain conditions: General Practitioners’ management of Fibromyalgia - Pastor, Mª Angeles; López-Roig, Sofía; Johnston, Marie; Gracia, Rafael; Daza, Pablo (Anales de Psicología / Annals of Psychology, 2012)
Aims: In ambiguous chronic pain conditions, professional behaviour may be affected not only by scientific knowledge but also by beliefs about illness. In Spain, Fibromyalgia is the most frequent cause of chronic pain at Primary Care level. Our aims are to identify General Practitioners’ beliefs about Fibromyalgia, in terms of mental representation and clinical self-efficacy, and to study their relationships with patient management. Methods: 208 General Practitioners recruited on a voluntarily basis while attending educational workshops on Fibromyalgia, completed an adapted version of the Brief Illness Perception Questionnaire and ad hoc scales of clinical self-efficacy, clinical behaviour and satisfaction. Pearson correlation, multiple regression, t test and ANOVA were performed. Results: Doctors see Fibromyalgia as a severe condition and they perceived low control and moderate clinical self-efficacy. The main causes of Fibromyalgia were seen to be psychological. Regression analysis showed that mental representation components predicted clinical management with low explained variance (from 3% to 11%) while clinical self-efficacy predicted satisfaction with clinical management (from 46% to 61%). Conclusions: GPs self-efficacy and control perception of Fibromyalgia need to be enhanced. While FM continues to be an ambiguous condition, variations in clinicians´ cognitions will be important for the care patients receive.